Preliminary data on Brachyura in the Can Gio mangrove area, Ho Chi Minh City - Nhuong, Do Van (Academia Journal of Biology, 2015)
The Can Gio Mangrove area is a large coastal area. Initial results have identify 49 species of Brachyura, among them there are 2 freshwater species that immigrated from terrestrial area: Ranguna bousmichei and Ranguna longipes. Some species of the Ocypodidae family are dominant in mangrove. The distribution of Brachyura: almost Grapsidae are found in the inner of mangrove forest; Ocypodidae are outside of the forest and some places without mangrove trees. The distribution features of Brachyura are dependent on characteristics of different biotops. Dominanting on the outer of mangrove forest is the genus Uca; on the mangrove ground is the genus Sesarma and some species of Macrophthalmus are dominant at the low tide area, near the streams and canals and at mud surfaces. Up to now, some species of Ocypodidae have been found only in the South of Vietnam.